Exploring Lake Victoria ecosystem functioning using the Atlantis modeling framework. (December 2016) - Nyamweya, Chrispine; Sturludottir, Erla; Tomasson, Tumi; Fulton, Elizabeth A.; Taabu-Munyaho, Anthony; Njiru, Murithi; Stefansson, Gunnar
Abstract: Lake Victoria has experienced human induced pressures such as overfishing, introduction of alien species, increased eutrophication and climate change impacts. However, there is limited understanding of the system dynamics, major processes, drivers and responses to the changes. To address this challenge, we developed the first end-to-end whole ecosystem model (Atlantis) for the lake. The model is spatially resolved into 12 unique dynamic areas based on depth, species composition, physical-chemical characteristics and fisheries management zones. A total of 38 functional groups constitute the biological model. Four fishing fleets with different targeting options are simulated. Reliability of the model is confirmed by the good fit of simulations output to observational data sets. Herein, we describe the evolution of the biophysical system, illustrating how it responded to the aforementioned induced perturbations since 1958. The constructed virtual Lake Victoria ecosystem model provides a platform for exploring the impact of management interventions before actual implementation. Highlights: Lake Victoria ecosystem functioning since 1958 is described. The importance of predator-prey interactions is highlighted. Introduced species show negative correlation with native species. The developed model can be used to "road test" fisheries management regimes.